Seven new species from Eocene Baltic amber reveal surprising diversity and suggest possible speciation scenarios in the relictual family Collohmanniidae (Acari: Oribatida) - Kolesnikov, Vasiliy B.; Vorontsov, Dmitry D.; Sidorchuk, Ekaterina A. (Zootaxa, 2024)
This study provides a comprehensive morphological analysis of ten fossil specimens from the genus Collohmannia, found in Eocene Baltic amber, with nine representing different species. Collohmanniidae, a unique monogeneric family of oribatid mites are among the largest oribatids. They feed on leaf litter and present significant sexual dimorphism and courtship behavior, which includes the transfer of nuptial food from male to female. Extant Collohmannia species inhabit isolated mountain forest areas. A fragmentation hypothesis has been proposed to account for their highly disjunctive distribution, suggesting that climate change divided a large forest area previously occupied by a parent species, leading to the allopatric evolution of several species of Collohmannia. However, with the discovery of a significant number of fossil species in Eocene Baltic amber we propose an alternate hypothesis with the Baltic amber forest serving as an arena for speciation of Collohmanniidae. According to it, the driving force of speciation was dietary and was based on gut microbiome specificity, reinforced by the female choice during the courtship ritual. In this paper we describe seven new fossil species of Collohmannia (C. sellnicki sp. nov., C. albertii sp. nov., C. nortoni sp. nov., C. groehni sp. nov., C. kerneggeri sp. nov., C. weiterschani sp. nov., C. clavata sp. nov.), re-describe C. schusteri based on study of the holotype, synonymize Embolacarus with Collohmannia, propose and describe the neotype of C. pergrata comb. nov., and provide a key to all described Collohmanniidae. Together with the hypotheses of speciation we propose verification experiments to be performed on extant Collohmannia mites.